Investigation of the relationship between betatrophin and certain key enzymes involved in carbohydrate and lipid metabolism in insulin-resistant mice - Arikan, Funda Bulut; Ulas, Mustafa; Ustundag, Yasemin; Boyunaga, Hakan; Badem, Nermin Dindar (Walter de Gruyter Gmbh, 2023)
Objectives The present study sought to examine the relationship of betatrophin with certain key enzymes, namely lactate dehydrogenase-5 (LDH5), citrate synthase (CS), and acetyl-CoA carboxylase-1 (ACC1), in insulin-resistant mice.Methods Eight-week-old male C57BL6/J mice were used in this study (experimental group n=10 and control group n=10). S961 was administered using an osmotic pump to induce insulin resistance in the mice. The betatrophin, LDH5, CS, and ACC1 expression levels were determined from the livers of the mice using the real-time polymerase chain reaction (RT-PCR) method. Moreover, biochemical parameters such as the serum betatrophin, fasting glucose, insulin, triglyceride, total cholesterol, and high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol levels were analyzed.Results The betatrophin expression and serum betatrophin (p=0.000), fasting glucose, insulin, triglyceride (p <= 0.001), and total cholesterol (p=0.013) levels were increased in the experimental group. In addition, the CS gene expression level was statistically significantly decreased in the experimental group (p=0.01). Although strong correlation was found between the expression and serum betatrophin and triglyceride levels, no correlation was found between the betatrophin gene expression and the LDH5, ACC1, and CS gene expression levels.Conclusions The betatrophin level appears to play an important role in the regulation of triglyceride metabolism, while insulin resistance increases both the betatrophin gene expression and serum levels and decreases the CS expression level. The findings suggest that betatrophin may not regulate carbohydrate metabolism through CS and LDH5 or lipid metabolism directly through the ACC1 enzyme.
Keywords: acetyl-coa carboxylase; betatrophin; carbohydrate and lipid metabolism; citrate synthase; lactate dehydrogenase